Human resources management in family enterprises - Simonović Dragoljub (Trendovi u Poslovanju, 2022)
Family businesses play an important role in the economies of many countries. The family business is an area that is gaining more and more attention today among researchers, theorists, investors, policymakers and many others. The subject of this paper is to point out the specifics of human resource management in family businesses with reference to the media.